SRRM4 Expression and the Loss of REST Activity May Promote the Emergence of the Neuroendocrine Phenotype in Castration-Resistant Prostate Cancer - Zhang, Xiaotun (Clin Cancer Res, 2015)
PURPOSE: The neuroendocrine (NE) phenotype is associated with the development of metastatic castration-resistant prostate cancer (CRPC). Our objective was to characterize the molecular features of the NE phenotype in CRPC. EXPERIMENTAL DESIGN: Expression of chromogranin A (CHGA), synaptophysin (SYP), androgen receptor (AR), and prostate-specific antigen (PSA) was analyzed by immunohistochemistry (IHC) in 155 CRPC metastases from 50 patients and in 24 LuCaP prostate cancer patient-derived xenografts (PDX). Seventy-one of 155 metastases and the 24 LuCaP xenograft lines were analyzed by whole genome microarrays. REST splicing was verified by PCR. RESULTS: Co-expression of CHGA and SYP in >30% of cells was observed in 22 of 155 metastases (9 patients); 11 of the 22 metastases were AR+/PSA+ (6 patients), 11/22 were AR−/PSA− (4 patients), and 4/24 LuCaP PDXs were AR−/PSA−. By IHC, of the 71 metastases analyzed by whole genome microarrays, 5 metastases were CHGA+/SYP+/AR− and 5 were CHGA+/SYP+/AR+. Only CHGA+/SYP+ metastases had a NE transcript signature. The neuronal transcriptional regulator SRRM4 transcript was associated with the NE signature in CHGA+/SYP+ metastases and all CHGA+/SYP+ LuCaP xenografts. Additionally, expression of SRRM4 in LuCaP NE xenografts correlated with a splice variant of REST that lacks the transcriptional repressor domain. CONCLUSIONS: (a) metastatic NE status can be heterogeneous in the same patient, (b) the CRPC NE molecular phenotype can be defined by CHGA+/SYP+ dual positivity, (c) the NE phenotype is not necessarily associated with the loss of AR activity, and (d) the splicing of REST by SRRM4 could promote the NE phenotype in CRPC.